Heavy Lifting Causing Spontaneous Coronary Artery Dissection with Anterior Myocardial Infarction in a 54-Year-Old Woman - Yiangou, Kyriakos (Tex Heart Inst J, 2016)
Spontaneous coronary artery dissection in association with strenuous exercise and weightlifting is rather sparsely described in the medical literature. Diagnosis and treatment of this rare condition is a challenge, but prompt recognition and appropriate early choice of angioplasty or surgery can lead to a good outcome. We report the case of a postmenopausal 54-year-old woman who presented with anterior myocardial infarction caused by spontaneous dissection of the left anterior descending coronary artery after she had lifted a heavy weight while gardening. The patient was treated successfully by means of angioplasty and the implantation of 3 drug-eluting stents. In addition to presenting the patient's case, we review the topical medical literature.